Students' Responses in Learning Vocabulary through Audio-Lingual Method (ALM) at SMA Negeri 21 Makassar - Tria Ali; Nasmilah; Abidin Pammu (Pelopor Publikasi Akademika, 2023)
The audio-lingual method (ALM) is a prominent pedagogical strategy for English language instruction, with a particular emphasis on fostering oral proficiency and enhancing lexical acquisition. The purpose of this study is to determine how the audio lingual method affects vocabulary development. The researcher employed a quantitative methodology to assess students' proficiency with the audio-Lingual Method (AML) in vocabulary learning. In addition, the researcher employed quantitative methods and calculations using by SPSS 16.0 version. The analysis shows that the implementation of audio linguistic method in vocabulary improvement influenced significantly the students' interest in learning English. The students expressed a desire for both innovative teaching materials and an efficient teaching approach in order to increase the level of engagement in their English lessons